Urban Gravity Measurements for the Subsurface Investigation of Athens Basin (Greece) - Dilalos, S.; Alexopoulos, J.D. (Bulletin of the Geological Society of Greece, 2019)
Taking into consideration the major damage caused by the disastrous earthquake of 7th September 1999 (5.9R), the need for further and deeper investigation of the geological structure of the subsurface came up. The damage distribution of an earthquake is usually related to the tectonic structures of the area (Dilalos and Alexopoulos, 2017). Unfortunately, since the areas are covered with artificial surfaces, such as buildings, industrial infrastructures, roads, bridges and generally artificial surfaces, the geological research is quite complicated. The missing geological information for the deep subsurface can only be retrieved using geophysical methods. Given the fact that the 54.5% of Athens basin is covered with artificial surfaces (Dilalos, 2018), not all the geophysical methods can be applied. The land gravity measurements seem like the most applicable method for such a deep geotectonic investigation.